KOMPETENSI MULTIKULTURAL BAGI KONSELOR SEKOLAH - Ramadhoni, Sri Rahmah; Bulantika, Siti Zahra (LPPM STKIP PGRI Bandar Lampung, 2020)
Instructions Cultural differences, backgrounds and mindsets can lead the differences in the relationship counseling process. The existence of cultural diversity is a reality of life that can affect the individual life and all human activities, including activities in counseling. Multicultural counseling involves cross-racial and ethnic counseling relationships as a counselor must have multicultural competencies related to awareness of cultural assumptions, values, and biases of various cultural identities, and races. The focus of this article is to explore what is involved in being competent in multicultural counselors regarding the importance of developing multicultural competencies for school counselors, by: (a) explaining multicultural counseling, (b) outlining multicultural competency development instruments, (c) explaining competency development multicultural for school counselors.